2014
DOI: 10.1159/000363045
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Myocardial Histopathology and Morphometry in Rats with Adenine - Induced Chronic Renal Failure: Influence of Gum Acacia

Abstract: Background/Aim: Chronic kidney disease (CKD) is associated with increased occurrence of cardiovascular system dysfunction. Previous studies have revealed a number of alterations in the kidneys and heart during CKD. However, unbiased quantitative studies on these structures in this disease have so far not been addressed. Materials and Methods: We induced CKD in rats by feeding adenine (0.75% w/w, four weeks) and using unbiased stereological methods, investigated the effect of the ensuing CKD on the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
(38 reference statements)
5
18
0
Order By: Relevance
“…The kidneys from the control and chrysintreated rats appeared normal. However, the kidneys of adenine-treated rats were pale and with white crystals, similar to that described before [14][15][16]. The appearance of the kidneys of rats treated with adenine plus the three doses of chrysin were improved compared with the kidneys of rats treated with adenine alone.…”
Section: Physiological Datasupporting
confidence: 80%
“…The kidneys from the control and chrysintreated rats appeared normal. However, the kidneys of adenine-treated rats were pale and with white crystals, similar to that described before [14][15][16]. The appearance of the kidneys of rats treated with adenine plus the three doses of chrysin were improved compared with the kidneys of rats treated with adenine alone.…”
Section: Physiological Datasupporting
confidence: 80%
“…We have previously shown that induction of CKD with adenine in rats results in a significant increase in blood pressure and in histological and morphometric cardiac damage . In the present work, we have shown that curcumin was effective in dose‐dependently ameliorating the rise in blood pressure in rats with adenine‐induced CKD.…”
Section: Discussionsupporting
confidence: 65%
“…We have previously shown that induction of CKD with adenine in rats results in a significant increase in blood pressure [18] and in histological and morphometric cardiac damage [8].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, adenine-induced CRF in rats was adopted as a disease model for the evaluation of the effect of H 2 S on CRF. The results showed that the rats fed on the adenine diet for 4 weeks showed increased water intake, urine production, urinary protein, and relative kidney weight, which were similar to the signs and symptoms in rats with adenine-induced CRF 41, 42 . In addition, a previous study has reported a reduction in body weight in adenine-fed rats which could be attributed to the reduced food consumption 43 .…”
Section: Discussionsupporting
confidence: 52%